Properties of cultivated soil from Mesilou-Kundasang agricultural area - Sahibin Abd Rahim; Ng Siuw Sing; Diana Demiyah Mohd Hamdan; Junaidi Asis; Hennie Fitria Wulandari Soehadi Erfen; Nur Zaida Zahari; Baba Musta (e-VIBS, Faculty of Science and Natural Resources, 2021)
A study to examine the physical properties of soil used to cultivate Allium plant from Kundasang-Mesilou agricultural area was carried out. Six sampling stations covering different types of parent materials were chosen. Topsoil’s samples from these stations were examined for their physico-chemical properties using standard method for soil analysis. From the result of this research showed that sufficient content of organic matter, low soil bulk density indicating a good soil structure, high available macronutrient contents, low cation exchange capacity and a non-saline electrical conductivity. The dominant soil texture were loamy with some were clayey and sandy. In general the physical properties of soil were suitable for vegetables cultivation but the chemical properties shown it required conventional input to satisfy plant needs. The overall physico-chemical properties of soils in the study area at present were less fertile compared to their properties fifteen years ago. The soil physico-chemical properties also deteriorated compared to the forested area.